Realization of polyurethane/epoxy interpenetrating polymer networks with a broad high-damping temperature range using β-cyclodextrins as chain extenders. (15th December 2021) - Feng, Qiang; Shen, Menglu; Zhu, Jiaming; Li, Jiang; Zhang, Jie; Guo, Shaoyun
Graphical abstract: Different structure of PU/EP IPNs crosslinked by TMP or β-CDs and its effect on damping performance. Highlights: Innovative use of β-cyclodextrins as polyurethane chain extenders and epoxy as the second phase achieved a broad high-damping temperature range. β-cyclodextrins grafting different numbers of polyurethane chains generated different-size motion units and broadened the damping temperature range. Because motion units ranged randomly, much interface friction occurred among surrounding motion units and improved the damping value. The unreacted hydroxyls on β-cyclodextrins formed hydrogen bonds with urethane groups, thus facilitating an increase in the damping value. Abstract: Damping materials, especially high-damping (loss factor (tanδ) > 0.5 and above) materials, are widely applied for suppressing vibration and controlling noise in industrial field, but achieving a high tanδ over a wide temperature range is a challenging task. Herein, we report a novel polyurethane (PU)/epoxy (EP) interpenetrating polymer network (IPN) damping material by using 21-hydroxyl β-cyclodextrins (β-CDs) as PU chain extenders. At a high ratio of hydroxyls to isocyanate groups, every β-CD underwent a different degree of chain expansion. Then these β-CDs grafting different numbers of PU chains generated different-size hard segments, thus increasing the species of motion units and widening the damping temperature range. The unreacted hydroxyls on β-CDs provided a large quantity of hydrogen bonding protons, which could form hydrogen bonds with urethane groups, thus facilitating an increase in the tanδ value. Therefore, PU/EP IPNs with a broad high-damping temperature range were successfully prepared. The results showed that PU/EP IPNs cured by β-CDs underwent a damping temperature range of 93.1 K (tanδ > 0.5), 82.4 K (tanδ > 0.7) and even 74.1 K (tanδ > 0.8), much better than the corresponding 32.9 K, 23.9 K and 20.5 K for traditional PU/EP IPNs cured by trihydroxyl trimethylolpropane (TMP).